Relaxation Techniques for Advancing Women-Centered Childbirth Care - Yulizawati, Yulizawati; Chairani, Yunita; Intasir, M. Pemberdi; Pramawahyudi, Pramawahyudi; Sari, Maharani Permata; Qalbi, Tajri Syayidil (Journal of Midwifery, 2025)
- Background: Contemporary maternity care emphasizes not only maternal and neonatal safety but also the quality of women’s childbirth experiences. However, increasing medicalization of labor has been associated with diminished maternal autonomy, heightened anxiety, and negative birth experiences. Women-Centered Care (WCC) offers a midwifery-led approach that prioritizes respect, empowerment, partnership, and individualized care. Within this framework, relaxation techniques serve as non-pharmacological strategies to support physiological labor and enhance maternal wellbeing. Objective: This narrative review aims to examine current evidence on relaxation techniques used during labor and their role in reducing pain and anxiety while promoting positive childbirth experiences in alignment with women-centered care principles. Methods: A narrative review of recent literature was conducted using PubMed, Wiley, Cochrane Library, and Google Scholar. Studies published within the last five years were included without restrictions on study design, focusing on relaxation techniques applied during intrapartum care. Results: The findings indicate that various relaxation techniques—including breathing exercises, manual techniques, music therapy, aromatherapy, and hydrotherapy—are effective in alleviating labor pain and anxiety. These interventions support neuroendocrine processes essential for physiological labor, enhance women’s sense of control, and improve overall childbirth satisfaction. Relaxation techniques also reinforce key components of WCC by fostering autonomy, comfort, and active participation in the birthing process. Conclusion: Relaxation techniques are effective, safe, and feasible interventions that support the implementation of women-centered childbirth care. Their integration into intrapartum midwifery practice can enhance maternal wellbeing, promote positive birth experiences, and strengthen respectful and holistic maternity care.